KAJIAN PEMBIAYAAN PERTANIAN PADI PADA STATUS PENGGUNAAN LAHAN YANG BERBEDA DI KABUPATEN LEBONG - Arma Putra; Widia Santika (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
This study aims to examine the sources of financing for rice farming on different land tenure status, examine the pattern of financing for rice farming in the research location and examine the factors that influence farmers in the utilization of financing sources. The method of determining the location by multistages sampling and the method of determining the sample is stratified purposive sampling. Data analysis used descriptive analysis and probit regression model (probability unit). The results showed that 64% of sharecroppers and 57% of sharecroppers used independent sources of capital, while 26% of sharecroppers and 33% of sharecroppers used loan capital and the other 10% used shared capital. Sources of financing for farmer loans, namely neighbors with a pattern of loan repayments, do not have special requirements and the repayment period is relatively long. Factors that influence farmers in utilizing sources of financing for their rice farming are education, land area and land tenure status. Education has a positive effect on the use of financing sources, while land area and land tenure status have a negative effect.